2006
DOI: 10.1093/jn/136.3.582
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Intake of High-Fat and High-Sucrose Diets Differentially Affects Glucose Intolerance in Mice

Abstract: Intakes of some macronutrients can comprise risk factors for life-style-related diseases such as obesity, hyperlipidemia, diabetes, hypertension, and atherosclerosis. In this study, we examined the effects in C57BL/6J mice of consuming excess fat or sucrose for a long period of time (55 wk). Another group of mice consumed a low-fat, low-sucrose (LL) diet. Mice fed the high-fat (HF) diet gained weight and developed hyperlipidemia and hyperleptinemia. At 25 wk, but not at 55 wk, hepatic glucose-6-phosphatase (G6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
114
4
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(146 citation statements)
references
References 44 publications
22
114
4
6
Order By: Relevance
“…Increased brite adipocyte levels and hyperexpression of ectopic UCP-1 confer resistance to diet-induced obesity (42,43), as probably occurs in the undernourished rats. Dyslipidemia, Ectopic Lipids, and Oxidative Stress-The cafeteria formula did not modify either triglyceridemia or cholesterolemia in the control rats, in contrast to other regimes richer in fat (44). When the undernourished were transferred to lab chow, their reduced triglyceride levels persisted.…”
Section: Discussionmentioning
confidence: 91%
“…Increased brite adipocyte levels and hyperexpression of ectopic UCP-1 confer resistance to diet-induced obesity (42,43), as probably occurs in the undernourished rats. Dyslipidemia, Ectopic Lipids, and Oxidative Stress-The cafeteria formula did not modify either triglyceridemia or cholesterolemia in the control rats, in contrast to other regimes richer in fat (44). When the undernourished were transferred to lab chow, their reduced triglyceride levels persisted.…”
Section: Discussionmentioning
confidence: 91%
“…Commonly used rat models are spontaneous hypertensive rats and Sprague Dawley rats, both strains fed with high-sugar diet (33). Although high-fat diet models and high-sucrose models have different effects on the metabolism, both facilitate metabolic disorders (34). Spontaneous HTG rats and HTG rats fed high-fat diet both resemble signs of the metabolic syndrome (31).…”
Section: Discussionmentioning
confidence: 99%
“…Solid food with a normal fat content failed to induce obesity and hyperinsulinemia in C57BL/6J mice (Sumiyoshi et al, 2006). However, a recent study demonstrated that although a sucrose-rich diet (32%) does not lead to obesity in C57BL/6 mice, the diet has the potential to cause changes in adipocytes (hypertrophy), as well as glucose intolerance, hyperinsulinemia, hyperlipidemia, hepatic steatosis and increased levels of inflammatory cytokines (Oliveira et al, 2014).…”
Section: Sucrose Dietmentioning
confidence: 99%